A polymorphic form of 4, 4‐dimethyl‐8‐methylene‐3‐azabicyclo[3.3.1]non‐2‐en‐2‐yl 3‐indolyl ketone, an indole alkaloid extracted from Aristotelia chilensis (maqui). (12th November 2013) - Paz, Cristian; Becerra, José; Silva, Mario; Freire, Eleonora; Baggio, Ricardo
<x xml:space="preserve">Abstract</x> The title compound [systematic name: (4, 4‐dimethyl‐8‐methylene‐3‐azabicyclo[3.3.1]non‐2‐en‐2‐yl)(1H‐indol‐3‐yl)methanone], C20H22N2O, (II), was obtained from mother liquors extracted from Aristotelia chilensis (commonly known as maqui), a native Chilean tree. The compound is a polymorphic form of that obtained from the same source and reported by Watson, Nagl, Silva, Cespedes & Jakupovic [Acta Cryst. (1989), C45, 1322–1324], (Ia). The molecule consists of an indolyl ketone fragment and a nested three‐ring system, with both groups linked by a C—C bridge. Comparison of both forms shows that they do not differ in their gross features but in the relative orientation of the two ring systems, due to different rotations around the bridge, as measured by the O=C—C=N torsion angle [130.0 (7)° in (Ia) and 161.6 (2)° in (II)]. The resulting slight conformational differences are reflected in a number of intramolecular contacts being observed in (II) but not in (Ia). Regarding intermolecular interactions, both forms share a similar N—H...O synthon but with differing hydrogen‐bonding strength, leading in both cases to C(6) catemers with different chain motifs. There are marked differences between the two forms regarding colour and the (de)localization of a double bond, which allows speculation about the possible existence of different variants of this type of molecule.